Faktor - Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Masa Prakonsepsi Di Puskesmas Kecamatan Jagakarsa Tahun 2023 - Siti Patonah; Wiwin Nur Fitriani; Eka Bati Widyaningsih (Indonesian Journal of Midwifery Scientific, 2024)
Background: Anemia is still a public health problem globally. Women of Childbearing Age (WUS) are an age group with a fairly high prevalence of anemia. Premarital WUS iron status is a very important factor for determining maternal and neonatal outcomes during pregnancy, childbirth and puerperium. If a woman already has anemia during preconception, then she is more at risk of anemia during pregnancy. Therefore, anemia must be severed starting from the preconception period so that it does not progress to the next stage of the life cycle. Objective: Determine the factors associated with the incidence of anemia during the preconception period at the Jagakarsa District Health Center in 2023. Methodology: The design used in this study is descriptive analytic by using secondary data of primary data conducted through a cross sectional approach to determine between independent variables (age, education, occupation, chronic energy deficiency status (SEZ), consumption of blood added tablets (TTD) and knowledge) with dependent variables (incidence of anemia). Results: age with the incidence of anemia with a significancy value on the results showing (p = 0.682 > 0.05), last education with the incidence of anemia, with a significancy value on the results showing (p = 0.006 < 0.05), occupation with the incidence of anemia with a significancy value on the results showing (p = 0.012 < 0.05), Chronic Energy Deficiency (SEZ) status with the incidence of anemia with a significancy value on the results showing (p = 0.035 < 0.05), Consumption of Blood Add Tablets with the incidence of anemia with a significancy value on the results showing (p = 0.027 < 0.05), knowledge with the incidence of anemia with a significancy value on the results showing (p = 0.005 < 0.05). Conclusions and Suggestions: there is no relationship between age and the incidence of anemia, and there is a relationship between work, education, SEZ status, consumption of blood added tablets, and knowledge with the incidence of anemia in the preconception period at the Jagakarsa Health Center in 2023 Keywords: anemia, age, education, occupation, SEZ status, consumption of blood added tablets, knowledge Bibliography: WHO 2021